Host Plants Influence the Symbiont Diversity of Eriosomatinae (Hemiptera: Aphididae) - Ting-Ting Xu; Li-Yun Jiang; Jing Chen; Ge-Xia Qiao (Insects, 2020)
Eriosomatinae is a particular aphid group with typically heteroecious holocyclic life cycle, exhibiting strong primary host plant specialization and inducing galls on primary host plants. Aphids are frequently associated with bacterial symbionts, which can play fundamental roles in the ecology and evolution of their host aphids. However, the bacterial communities in Eriosomatinae are poorly known. In the present study, using high-throughput sequencing of the bacterial 16S ribosomal RNA gene, we surveyed the bacterial flora of eriosomatines and explored the associations between symbiont diversity and aphid relatedness, aphid host plant and geographical distribution. The microbiota of Eriosomatinae is dominated by the heritable primary endosymbiont Buchnera and several facultative symbionts. The primary endosymbiont Buchnera is expectedly the most abundant symbiont across all species. Six facultative symbionts were identified. Regiella was the most commonly identified facultative symbiont, and multiple infections of facultative symbionts were detected in the majority of the samples. Ordination analyses and statistical tests show that the symbiont community of aphids feeding on plants from the family Ulmaceae were distinguishable from aphids feeding on other host plants. Species in Eriosomatinae feeding on different plants are likely to carry different symbiont compositions. The symbiont distributions seem to be not related to taxonomic distance and geographical distance. Our findings suggest that host plants can affect symbiont maintenance, and will improve our understanding of the interactions between aphids, their symbionts and ecological conditions.